A proposal for an intensive Cherry Orchard in Khachmaz region - Rasulova, Asmar (ADA University, 2020)
The agricultural sector in Azerbaijan is one of the fastest-growing ones due to some intense arguments. First of all, the favorable climatic conditions within the country, with the existence of nine out of eleven climatic zones, which plays as an accelerator for agro-business initiatives. Secondly, the path of diversification undertaken by the government in order to weaken the dependence on the oil&gas sector. The tax exemptions and privileges given to the entrepreneurs, simplified procedure for the company registration as well as the big consumer market nearby create a favorable environment for investments. The sweet cherry production in Azerbaijan is a particular part of the agricultural business, which gains considerable attention due to the increasing volume of export majorly to the Russian market. The product shows sustainable demand due to its seasonability and specific taste, which is in favor of Russian consumers. Within the framework of the given study, we attempted to reveal the potential advantages of an intensive sweet cherry orchard with proper evaluation of financial projections. The study involved the business insider attributes for the discussed business with the large amount of data found through several secondary data sources. Based on our interviews with business-involved persons as well as data on distinctive aspects, assist in the development of this business plan. As a result, we observed the vacant niche in the supplier chain, which creates a chance for us to succeed in this business. Moreover, we were able to find that sales channels and relationships established with people are the major part of the entity’s success.
Keywords: Business; Agricultural sector -- Azerbaijan.; Agricultural business -- Azerbaijan.; Azerbaijan -- Economic conditions.; Russia (Federation) -- Economic conditions.